A Case Study on Neurological Outcome in Persistent Neonatal Hypoglycemia in Upper Middle-Income Country - Primadi, Aris; Yuniati, Tetty; Aprilia Kadi, Fiva; Reviyani Suryaningrat, Filla; Hudayari, Devatri; Ediwan, Natasha Amalda (Faculty of Medicine, Universitas Padjadjaran, 2024)
In Indonesia, comprehensive management and monitoring of persistent neonatal hypoglycemia, is rarely reported. Despite the fact that there are studies highlighting the risk of neurodevelopmental disorders in neonates with hypoglycemia, there seems to be limited comprehensive case reports detailing both the early diagnosis and the long-term growth and development monitoring in these neonates. A unique case report of a 10-day-old male baby, born at a term weeks gestation via caesarean section, diagnosed with persistent hypoglycemia and suspect of hyperinsulinemia is presented in this study. At birth, the neonate exhibited hypoglycemia with a blood glucose level of 25 mg/dL, accompanied by a one-minute seizure characterized by upward gaze and stiffening of the extremities. The neonate cried after seizure and there was no loss of consciousness and was admitted to the NICU due to worsening respiratory distress. Based on the thoracic X-ray examination, he was diagnosed with transient tachypnea of newborn (TTN). Blood glucose levels were monitored every four hours, and tests for cortisol, thyroid and growth hormone and routine urinalysis were planned. Total parenteral nutrition (TPN) were given with intravenous antibiotics. At 6months of age, the infant was diagnosed with intellectual disability by the growth and development social pediatric unit. At 7 months, the infant began undergoing physiotherapy. This case was followed for 7 months in total and the findings highlight the challenges in managing neonatal persistent hypoglycemia and the potential long-term developmental implications in neonates with early-life hypoglycemia, emphasizing the need for continual growth and development monitoring.